2015
DOI: 10.1007/s00425-015-2414-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and metabolomic analysis of Punica granatum (L.) under drought stress

Abstract: Punica granatum has a noticeable adaptation to drought stress. The levels of the green leaf volatile trans-2-hexenal increased in response to drought stress suggesting a possible role of this compound in drought stress response in pomegranate. Punica granatum (L.) is a highly valued fruit crop for its health-promoting effects and it is mainly cultivated in semi-arid areas. Thus, understanding the response mechanisms to drought stress is of great importance. In the present research, a metabolomics analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 28 publications
2
20
0
2
Order By: Relevance
“…Under the tested stress factor, an increase in H 2 O 2 and MDA levels indicates this cellular damage in A. orientalis. Several cellular protectants can be accumulated to regulate the cellular redox status under drought stress due to excessive H 2 O 2 production (Catola et al, 2016). Also, activities of ROS-scavenging enzymes are triggered by H 2 O 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Under the tested stress factor, an increase in H 2 O 2 and MDA levels indicates this cellular damage in A. orientalis. Several cellular protectants can be accumulated to regulate the cellular redox status under drought stress due to excessive H 2 O 2 production (Catola et al, 2016). Also, activities of ROS-scavenging enzymes are triggered by H 2 O 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the other GLVs, 2-Hal plays an important role in inducing oxidative stress responses, which suggests that RSLVs, including 2-Hal, are abiotic stress-related infochemicals, and, thus, 2-Hal emission is enhanced by abiotic stresses such as heat 26) and drought. 27) On the contrary, gene expression data obtained using the Agilent array indicated that 2-Hal downregulated a group of genes related to auxin metabolism, possibly accounting for the ability of 2-Hal to inhibit root elongation. 28)…”
Section: Effects Of 2-hexenal (2-hal 2) On Gene Expressionmentioning
confidence: 99%
“…Drought stress is one of the most serious abiotic stresses, which can lead to serious damage to plants including stomata closure, limitation of photosynthesis and inhibition of physiological functions such as antioxidant functions [6][7][8]. Under drought stress, plants will regulate the morphology, physiology and metabolism to adapt to a water deficit environment [9].…”
Section: Introductionmentioning
confidence: 99%